Ruthenium-Benzothiadiazole Building Block Derived Dynamic Heterometallic Ru-Ag Coordination Polymer and Its Enhanced Water-Splitting Feature - Dey S.; Singh B.; Dasgupta S.; Dutta A.; Indra A.; Lahiri G.K. (My University, 2025)
This article deals with the development of the unprecedented redox-mediated heterometallic coordination polymer {[RuIII(acac)2(μ-bis-η1-N,η1-N-BTD)2AgI(ClO4)]ClO4}n (3) via the oxidation of the monomeric building block cis-[RuII(acac)2(η1-N-BTD)2] (1) by AgClO4 (BTD = exodentate 2,1,3-benzothiadiazole, acac = acetylacetonate). Monomeric cis-[RuII(acac)2(η1-N-BTD)2] (1) and [RuII(acac)2(η1-N-BTD)(CH3CN)] (2) were simultaneously obtained from the electron-deficient BTD heterocycle and the electron-rich metal precursor RuII(acac)2(CH3CN)2 in refluxing CH3CN. Molecular identities of 1-3 were authenticated by their single-crystal X-ray structures as well as by solution spectral features. These results also reflected the elusive trigonal-planar geometry of the Ag ion in Ru-Ag-derived polymeric 3. Ru(III) (S = 1/2)-derived 3 displayed metal-based anisotropic EPR with g = 2.12/0.56 and paramagnetically shifted 1H NMR. Spectroelectrochemistry in combination with DFT/TD-DFT calculations of 1n and 2n (n = 1+, 0, 1-) determined a metal-based (RuII/RuIII) oxidation and BTD-based reduction (BTD/BTD-). The drastic decrease in the emission intensity and quantum yield but insignificant change in the lifetime of 3 with respect to 1 could be addressed in terms of static quenching and/or a paramagnetism-induced phenomenon. A homogeneously dispersed dumbbell-shaped morphology and the particle diameter of 3 were established by microscopic (TEM-EDX/SEM) and DLS analysis, respectively. Moreover, the dynamic nature of polymeric 3 was highlighted by its degradation to the η1-N-BTD coordinated monomeric fragment 1, which could also be followed spectrophotometrically in polar protic EtOH. Interestingly, both monomeric 1 and polymeric 3 exhibited efficient electrocatalytic activity toward water oxidation processes (OER, HER) on immobilization on an FTO support, which also divulged the better intrinsic water oxidation activity of 3 in comparison to 1. © 2021 American Chemical Society.